Honeycomb structure and method for manufacturing honeycomb structure
By coating the magnetic particle slurry containing Si, Al and Mg on the surface of the substrate compartment of the honeycomb structure and firing it, an optimized coating layer is solved, resulting in uneven coating thickness and burning shrinkage. The problem of reducing heat shock resistance has achieved high heat shock resistance and repeated durability.
Patent Information
- Application Number
- CN202410734668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-11
- Filing Date
- 2024-06-07
- Publication Date
- 2025-01-14
AI Technical Summary
The existing honeycomb structure has problems with voids caused by uneven coating thickness and scaling shrinkage, resulting in reduced heat impact resistance and prone to cracks.
The magnetic particle slurry containing Si, Al and Mg is coated on the surface of the target compartment of the substrate, and a coating layer is formed by firing, controlling the relative density, thickness and thickness ratio of the coating layer, and optimizing the magnetic particle Connectivity and structure, reducing the amount of burning shrinkage.
The heat shock resistance and repeated durability of the honeycomb structure are improved, cracks caused by stress concentration on the coating layer and compartment surface are suppressed, and the stability of thermal expansion is enhanced.
Smart Images

Figure CN119306512A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a honeycomb structure and a method for manufacturing the honeycomb structure. Background Art
[0002] In the past, there is a known method of induction heating that uses electromagnetic induction to heat the object to be heated. Induction heating is performed as follows: an induction heating coil is arranged near the object to be heated that includes a magnetic material or a conductive material, and the induction heating coil is used to generate a magnetic field, thereby performing induction heating. For example, when heating a columnar object to be heated, an induction heating coil is provided that surrounds the outer periphery of the object to be heated. For example, the alternating current from a high-frequency converter is amplified by a transformer, thereby obtaining a current that flows through the induction heating coil when a magnetic field is generated. Since the object to be heated can be heated in a non-contact manner, induction heating is particularly useful in the case of heating materials with low thermal conductivity or in the case of heating an object under conditions where thermal contact is not easy to implement. In addition, compared with indirect heating using heat conduction, it is direct heating using self-heating, so the energy efficiency is also good.
[0003] In addition, there is also a known technology for heating a catalyst carrier by induction heating. For example, in the catalyst carrier of Patent Document 1, metal particles are introduced into the inner space of a selected compartment in a ceramic substrate having a plurality of compartments. The metal particles are fixedly bonded to each other and to the ceramic substrate by a fixing bonding material. The metal particles generate heat according to changes in the magnetic field.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-188272 Summary of the invention
[0007] However, when a coating layer containing magnetic particles is provided on the surface (inner surface) of the cell of the substrate, the thickness of the coating layer sometimes becomes uneven. For example, when the cross-sectional shape of the cell is roughly square, the thickness of the coating layer at the corner of the cell becomes larger than other parts due to the influence of the surface tension of the slurry when the slurry containing magnetic particles is applied. In addition, due to the influence of sintering shrinkage, a larger gap is generated between the surface of the corner and the coating layer. In this case, if the thermal shock resistance is evaluated, stress concentration occurs at the boundary of the contact portion and the non-contact portion (the above-mentioned gap) between the coating layer and the cell surface, and cracks are generated in the substrate. Like this, the thermal shock resistance of the honeycomb structure provided with a coating layer is reduced.
[0008] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a honeycomb structure having high thermal shock resistance.
[0009] The invention of Scheme 1 is a honeycomb structure, which comprises: a substrate, which is a cylindrical part and has a plurality of compartments extending from one end face to another end face; and a coating layer, which is arranged on the surface of at least a part of the plurality of compartments, namely the target compartments, and is obtained by combining magnetic particles with each other, and the coating layer contains at least one element of Si, Al and Mg as an additive element, and in the coating layer, the ratio of the sum of the weight fractions of the additive elements to the sum of the weight fractions of the main constituent elements of the magnetic particles is 1.7wt% or more.
[0010] The invention according to claim 2 is the honeycomb structure according to claim 1, wherein the main constituent elements of the magnetic particles are Fe and Cr.
[0011] The invention according to claim 3 is the honeycomb structure according to claim 1 or 2, wherein in the coating layer, the compound containing the additional element is present on the surface of the magnetic particles.
[0012] The invention according to claim 4 is the honeycomb structure according to any one of claims 1 to 3, wherein the relative density of the coating layer is 75 to 95%.
[0013] The invention according to claim 5 is the honeycomb structure according to any one of claims 1 to 4, wherein the coating layer has a thickness of 20 to 100 μm.
[0014] The invention according to claim 6 is the honeycomb structure according to any one of claims 1 to 5, wherein the maximum width of the gap between the surface of the target cell and the coating layer is 15 μm or less.
[0015] The invention of Scheme 7 is based on the honeycomb structure of any one of Schemes 1 to 6, wherein the coating layer has: a thick portion with a locally maximum thickness, and a thin portion with a locally minimum thickness, and the ratio of the thickness of the thick portion to the thickness of the thin portion is less than 2 times.
[0016] The invention of Scheme 8 is a method for manufacturing a honeycomb structure, which includes the following steps: a) preparing a substrate, which is a cylindrical part and has a plurality of compartments extending from one end face to another end face; b) preparing a slurry containing magnetic particles and clay minerals; c) applying the slurry on the surface of at least a portion of the plurality of compartments, i.e., the target compartments; and d) drying and sintering the slurry applied to the target compartments, thereby forming a coating layer on the surface of the target compartments.
[0017] The invention according to claim 9 is the method for producing a honeycomb structure according to claim 8, wherein the clay mineral includes at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite, and attapulgite.
[0018] Effects of the Invention
[0019] According to the present invention, a honeycomb structure having high thermal shock resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a cross-sectional view showing the structure of an induction heating device.
[0021] Figure 2 is a plan view showing a honeycomb structure.
[0022] Figure 3 is a cross-sectional view showing a subject compartment and its vicinity.
[0023] Figure 4 is a cross-sectional view showing a coating layer at a corner.
[0024] Figure 5 is a cross-sectional view showing the coating layer at the flat surface portion.
[0025] Figure 6 is a cross-sectional view showing a coating layer at a corner.
[0026] Figure 7 is a cross-sectional view showing a coating layer at a corner.
[0027] Figure 8 It is a figure which shows the manufacturing flow of a honeycomb structure.
[0028] Fig. 9 This is a diagram showing how the slurry is applied to the target cell.
[0029] Fig. 10A is a SEM image of a subject cell showing that the thickness of the coating layer is less than 20 μm.
[0030] Fig. 10B : is a SEM image showing a subject cell in which the thickness of the coating layer is 20 μm or more.
[0031] Fig.11A is an SEM image of a subject cell showing that the thickness ratio of the thick portion relative to the thin portion is greater than 2 times.
[0032] Fig. 11B This is an SEM image showing a target cell in which the thickness ratio of the thick portion to the thin portion is 2 times or less.
[0033] Fig.12 is a diagram showing an induction heating coil.
[0034] Explanation of symbols
[0035] 1...honeycomb structure, 2...substrate, 3...coating layer, 23...compartment, 23a...target compartment, 29...end face (of substrate), 31...magnetic particles, 36...thick portion, 37...thin portion, 239...corner gap, S11 to S14...steps. DETAILED DESCRIPTION
[0036] Figure 1 2 is a cross-sectional view showing the structure of the induction heating device 4. The induction heating device 4 is provided in a flow path 9 of exhaust gas discharged from an engine of an automobile or the like. The induction heating device 4 includes an exhaust gas purification unit 41, a coil unit 42, and a fixing member 43. The exhaust gas purification unit 41 includes a honeycomb structure 1 as a catalyst carrier and a catalyst supported on the honeycomb structure 1. The honeycomb structure 1 is a cylindrical member having a plurality of cells 23 extending along the flow path 9 (see the following description). Figure 2 ). The exhaust gas flows in the plurality of cells 23. The catalyst in the exhaust gas purifying unit 41 may be, for example, a noble metal-based catalyst or a catalyst that does not use a noble metal. The honeycomb structure 1 will be described in detail below.
[0037] The coil portion 42 is a wire formed in a spiral shape, which surrounds the honeycomb structure 1. The fixing component 43 fixes the exhaust gas purification unit 41 and the coil portion 42 in the flow path 9. The coil portion 42 is connected to an AC power source not shown in the figure, and an AC current flows through the coil portion 42, thereby generating a periodically changing magnetic field around the coil portion 42. As described later, magnetic particles are contained in the interior of the honeycomb structure 1, and the honeycomb structure 1 is heated according to the change of the magnetic field. By heating the honeycomb structure 1, the temperature of the catalyst is also increased, and the catalytic reaction is promoted.
[0038] Figure 2 This is a simplified plan view of the honeycomb structure 1. As described above, the honeycomb structure 1 is a cylindrical member that is long in one direction. Figure 2 The length direction of the honeycomb structure 1 is shown in Figure 1 The left and right directions in Figure 2 The honeycomb structure 1 in the following description is in a state where no catalyst is loaded.
[0039] The honeycomb structure 1 includes a substrate 2 and a coating layer 3. The substrate 2 is a cylindrical member formed of a porous sintered body and has two end faces 29 in the longitudinal direction (see Figure 1). The substrate 2 includes a cylindrical outer wall 21 and a partition wall 22. The cylindrical outer wall 21 is a cylindrical portion extending in the longitudinal direction. The cross-sectional shape of the cylindrical outer wall 21 perpendicular to the longitudinal direction is, for example, roughly circular. The cross-sectional shape may also be other shapes such as a polygon.
[0040] The partition wall 22 is a lattice-shaped part arranged inside the cylindrical outer wall 21 and dividing the inside into a plurality of compartments 23. The plurality of compartments 23 are respectively spaces extending in the length direction. Each compartment 23 extends from one end face 29 to another end face 29. The catalyst described above is introduced into the compartment 23. The cross-sectional shape of each compartment 23 perpendicular to the length direction is, for example, roughly square. The cross-sectional shape may also be other shapes such as polygonal or circular. In principle, the plurality of compartments 23 have the same cross-sectional shape. The plurality of compartments 23 may also include compartments 23 of different cross-sectional shapes. The substrate 2 is a compartment structure whose interior is divided into a plurality of compartments 23 by the partition wall 22.
[0041] The cylindrical outer wall 21 and the partition wall 22 are respectively porous parts. The cylindrical outer wall 21 and the partition wall 22 are formed of ceramics such as cordierite. The material of the cylindrical outer wall 21 and the partition wall 22 can also be a ceramic other than cordierite, and can also be a material other than ceramics. Typically, the material has insulating properties.
[0042] The porosity of the substrate 2 including the cylindrical outer wall 21 and the partition wall 22 is, for example, 20% or more, preferably 30% or more. The porosity of the substrate 2 is, for example, 80% or less, preferably 70% or less. The open porosity of the substrate 2 is, for example, 40% or more, preferably 55% or more. The open porosity of the substrate 2 is, for example, 65% or less. The porosity and open porosity of the substrate 2 can be measured by the Archimedean method.
[0043] The average pore size of the substrate 2 is, for example, 5 μm or more, preferably 8 μm or more. The average pore size of the substrate 2 is, for example, 30 μm or less, preferably 25 μm or less. The average pore size can be measured using a mercury intrusion instrument. The surface opening rate of the substrate 2 is, for example, 20% or more, preferably 25% or more. The surface opening rate of the substrate 2 is, for example, 60% or less, preferably 50% or less. The surface opening rate is the ratio of the area of the region where the pores on the surface of the substrate 2 are opened, which can be solved by performing image analysis on the SEM (scanning electron microscope) image of the surface. The SEM image is taken at, for example, 500 times.
[0044] The cell density of the substrate 2 (ie, the number of cells 23 per unit area in a cross section perpendicular to the longitudinal direction) is, for example, 10 cells / cm 2 More than, preferably 20 cells / cm 2 More than 30 cells / cm 2The cell density is, for example, 200 cells / cm 2 Below, preferably 150 cells / cm 2 the following. Figure 2 In the figure, the size of the compartment 23 is drawn larger than the actual size, and the number of the compartments 23 is drawn smaller than the actual size. The size and number of the compartments 23 can be changed in various ways.
[0045] The coating layer 3 is a porous sintered body and is disposed in a portion of the cells 23a (hereinafter referred to as "target cells 23a") among the plurality of cells 23. The coating layer 3 covers the entire circumference of the target cells 23a, and typically covers substantially the entire surface (i.e., the inner circumference) of the target cells 23a. The plurality of target cells 23a provided with the coating layer 3 are preferably evenly dispersed. Figure 2 In the example, there is at least one compartment 23 without the coating layer 3 between each target compartment 23a and one of the other target compartments 23a. Accordingly, the honeycomb structure 1 can be heated up quickly and the reaching temperature is also increased compared with the case where the coating layer 3 is formed in all the compartments 23. In fact, it is confirmed that in a honeycomb structure having 300 compartments, when the coating layer is formed only in 9, 21, 45, and 61 compartments located at approximately equal intervals in a non-adjacent manner, the temperature can be heated up quickly and the reaching temperature is also increased compared with the case where the coating layer is formed in all the compartments. According to the design of the honeycomb structure 1, all the compartments 23 can also be the target compartments 23a.
[0046] Figure 3 This is a cross-sectional view showing one target cell 23a and its vicinity, and shows a cross section perpendicular to the longitudinal direction. The "cross section" in this specification refers to a cross section perpendicular to the longitudinal direction of the honeycomb structure 1 unless otherwise specified. Figure 3 In the example, the cross-sectional shape of each compartment 23, 23a perpendicular to the longitudinal direction is substantially square. The inner peripheral surface of each compartment 23, 23a has four corners 231 and four planes 232. Two adjacent corners 231 in each compartment 23, 23a are connected by the plane 232. Each corner 231 is formed by the intersection of the lattice-shaped partition walls 22, and the plane 232 is formed by the portion between the intersections in the partition walls 22 (also called ribs).
[0047] Figure 4 is a cross-sectional view showing the coating layer 3 at the corner 231, Figure 5 2 is a cross-sectional view showing the coating layer 3 at the flat surface portion 232. The coating layer 3 is a layer formed by the magnetic particles 31 being bonded to each other by sintering. Figure 4 and Figure 5 In FIG. 1 , the magnetic particles 31 are schematically shown as circles. The magnetic particles 31 may be in the form of fine particles, and small pieces of magnetic material may also be regarded as magnetic particles.
[0048] The magnetic particles 31 are, for example, metal particles. The preferred magnetic particles 31 are formed of ferrite stainless steel, containing Fe (iron) and Cr (chromium) as main constituent elements. Here, the main constituent element is an element that accounts for more than 3wt% of the constituent elements of the magnetic particles 31. The magnetic particles 31 can be formed of other materials that can be inductively heated. For example, martensitic stainless steel, austenitic stainless steel, invar, and super invar can be used. The magnetic particles 31 can also be particles other than metal particles.
[0049] The coating layer 3 contains at least one element of Si, Al and Mg as an additional element. The additional element is an element not contained in the main constituent elements of the magnetic particles 31. In principle, the additional element is an element not contained in the magnetic particles 31, but sometimes it is inevitably contained in the magnetic particles 31 in the form of impurities. As described later, in the formation of the coating layer 3, a raw material containing the additional element is used together with the magnetic particles 31. Accordingly, in the coating layer 3, the ratio of the sum of the weight fractions of the additional elements to the sum of the weight fractions of the main constituent elements of the magnetic particles 31 (hereinafter referred to as "the ratio of the additional elements to the magnetic particles") is 1.7wt% or more. The weight fraction of each element is the ratio of the weight of the element to the weight of the coating layer 3.
[0050] For example, when the magnetic particles 31 are particles of ferrite stainless steel and the raw material containing the additive element is montmorillonite, the main constituent elements of the magnetic particles 31 are Fe and Cr, and the additive element includes all of Si, Al, and Mg. In this case, the ratio of the additive element to the magnetic particles is the ratio of the sum of the weight fractions of Si, Al, and Mg to the sum of the weight fractions of Fe and Cr. For example, when the coating layer 3 does not contain Mg, the additive elements are only Si and Al, and when the coating layer 3 does not contain Al, the additive elements are only Si and Mg.
[0051] As described later, in the honeycomb structure 1 in which the ratio of the additive element to the magnetic particles in the coating layer 3 is 1.7 wt % or more, the heat shock resistance is improved. When obtaining the ratio of the additive element to the magnetic particles, the cross section of the coating layer 3 is measured using EDS (energy dispersive X-ray analyzer) to obtain the weight fraction of each main constituent element of the magnetic particles 31 and the weight fraction of each additive element. Then, the sum of the weight fractions of the additive elements is divided by the sum of the weight fractions of the main constituent elements of the magnetic particles 31 to obtain the ratio of the additive element to the magnetic particles.
[0052] Typically, the compound containing the additive element exists on the surface of the magnetic particles 31. The surface of the magnetic particles 31 includes not only the surface of the magnetic particles 31 forming the outer edge of the coating layer 3, but also the interface between the pores formed inside the coating layer 3 and the magnetic particles 31. The compound does not contain, for example, the main constituent elements of the magnetic particles 31. The compound may also contain any of the main constituent elements of the magnetic particles 31. For example, by performing element mapping using EDS on the cross section of the coating layer 3, it can be confirmed whether the compound containing the additive element exists on the surface of the magnetic particles 31. The additive element may exist at the interface between the magnetic particles 31, or it may be dissolved in the crystalline phase of the magnetic particles 31.
[0053] The relative density of the coating layer 3 is, for example, 75% or more, preferably 80% or more. Accordingly, the connectivity of the magnetic particles 31 is ensured, and the reaching temperature of the honeycomb structure 1 achieved by induction heating can be increased. When the relative density of the coating layer 3 is too large, the thermal expansion of the coating layer 3 increases, which may affect the heat shock resistance of the honeycomb structure 1. The relative density of the coating layer 3 is, for example, 95% or less, preferably 90% or less. When obtaining the relative density of the coating layer 3, an SEM image (500 times) of the cross section of the coating layer 3 at the corner 231 is obtained, and the calculation range ( Figure 4 Next, in the SEM image, the calculation range A1 is binarized using a threshold value that can distinguish the white region representing the magnetic particles 31 from other regions, and the area ratio of the white region is obtained as the relative density of the coating layer 3.
[0054] In the formation of the coating layer 3 described later, the slurry is applied to the surface (inner peripheral surface) of the target cell 23a. Figure 3 As shown, when the cross-sectional shape of the target compartment 23a is a substantially square, due to the influence of the surface tension of the slurry, the thickness of the coating layer 3 is locally the smallest at the center (center of the plane portion 232) between two adjacent corners 231, and the portion of the coating layer 3 located at the center becomes the thin portion 37. In addition, at the corner 231, the thickness of the coating layer 3 is locally the largest, and the portion of the coating layer 3 located at the corner 231 becomes the thick portion 36. In the following description, when simply referring to "the thickness of the coating layer 3", it refers to the thickness of the thin portion 37 at the plane portion 232.
[0055] The thickness of the coating layer 3 (i.e., the thickness of the thin portion 37) is, for example, not less than 20 μm, preferably not less than 30 μm. Accordingly, the reaching temperature of the honeycomb structure 1 achieved by induction heating can be increased. When the thickness of the coating layer 3 is too large, the cost required for forming the coating layer 3 increases. The thickness of the coating layer 3 is, for example, not more than 100 μm, preferably not more than 80 μm. When measuring the thickness of the thin portion 37, an SEM image (500 times) showing a cross section of the coating layer 3 is obtained at the center between two adjacent corners 231 (the center of the plane portion 232). Then, parallel lines L1 and L2 (refer to FIG. 2 ) along the two surfaces of the coating layer 3 are set in the SEM image. Figure 5 ), and the distance D1 between the parallel lines L1 and L2 is measured as the thickness of the thin portion 37. It should be noted that, when there are abnormal concave or convex portions on the surface of the coating layer 3 shown in the SEM image, the parallel lines L1 and L2 along the surface are set in a state where the concave or convex portions are excluded.
[0056] In addition, the thickness of the thick portion 36 is preferably not too large compared to the thickness of the thin portion 37. The ratio of the thickness of the thick portion 36 to the thickness of the thin portion 37 is preferably 2 times or less, and more preferably 1.8 times or less. In this way, in the honeycomb structure 1 in which the thickness uniformity of the coating layer 3 is improved, the reduction in thermal shock resistance caused by the unevenness of the thickness can be suppressed. When measuring the thickness of the thick portion 36, as shown in FIG. Figure 6 As schematically shown, a SEM image (500 times) showing a cross section of the coating layer 3 is obtained at the corner 231. Next, a tangent line L3 is set in the SEM image, which has an inclination angle of 45° relative to the plane portion 232 and is tangent to the outer periphery of the thick portion 36, and the shortest distance D3 between the tangent line L3 and the inner periphery of the thick portion 36 is measured as the thickness of the thick portion 36.
[0057] It should be noted that when the cross-sectional shape of the target compartment 23a is a roughly regular polygon other than a roughly square, typically, in the coating layer 3, the portion opposite to the corner portion becomes a thick portion, and the central portion between two adjacent thick portions becomes a thin portion. When the cross-sectional shape of the target compartment 23a is a circle, similarly, a thick portion with the largest thickness locally (for example, within each range that divides the circumference into four equal parts) and a thin portion with the smallest thickness locally are generated by the formation method of the coating layer 3. In short, by making the ratio of the thickness of the thick portion to the thickness of the thin portion less than 2 times, the heat shock resistance can be more reliably improved.
[0058] As described above, the coating layer 3 is a sintered body, and therefore, sometimes a gap 239 (hereinafter referred to as "corner gap 239") is generated between the surface of the corner 231 of the target cell 23a and the coating layer 3 due to firing shrinkage. The width of the corner gap 239 is, for example, less than 15 μm, preferably less than 12 μm. In the evaluation of heat shock resistance described later, stress concentration occurs at the boundary between the contact portion and the non-contact portion (the above-mentioned corner gap 239) between the coating layer 3 and the cell surface, and therefore, in the honeycomb structure 1 having a smaller width of the corner gap 239, the heat shock resistance can be more reliably improved. The width of the corner gap 239 can be 0. It is also possible that a gap is generated between the surface of the target cell 23a and the coating layer 3 at a position other than the corner 231, but when the cross-sectional shape of the target cell 23a is approximately square, the width of the corner gap 239 is the maximum width of the gap between the surface of the target cell 23a and the coating layer 3.
[0059] When measuring the width of the corner gap 239, Figure 7 As schematically shown, a SEM image (500 times) showing a cross section of the coating layer 3 is obtained at the corner 231. Next, a tangent line L4 is set in the SEM image, which is tangent to the corner 231 (the inner peripheral surface of the target cell 23a) at an inclination angle of 45° relative to the plane portion 232, and the shortest distance D4 between the tangent line L4 and the outer periphery of the thick portion 36 is measured as the width of the corner void 239. In the case where the cross-sectional shape of the target cell 23a is other than a roughly square (polygonal, circular, etc.), the maximum width of the void between the surface of the target cell 23a and the coating layer 3 is 15 μm or less in the honeycomb structure 1, and the heat shock resistance can also be more reliably improved.
[0060] Next, an example of production of the honeycomb structure 1 will be described. Figure 8 1 is a diagram showing a manufacturing process of the honeycomb structure 1. In the manufacturing of the honeycomb structure 1, first, a substrate 2 is prepared (step S11). The substrate 2 is provided with a plurality of cells 23 extending from one end face 29 to the other end face 29 (see Figure 1 and Figure 2 As a method for producing the substrate 2, various known methods can be used. Typically, the substrate 2 is produced by extrusion molding, drying and sintering of a blank.
[0061] Next, a slurry for coating layer formation is prepared (step S12). In the preparation of the slurry, magnetic particles as magnetic powder, powder of clay mineral, and dispersion medium (here water) are weighed and mixed in a container. As magnetic particles, powders of the materials described above can be used. Clay minerals are layered minerals, preferably comprising at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite and attapulgite. The slurry containing clay minerals has increased shear strength and viscosity compared to the slurry containing no clay minerals.
[0062] The amount of clay mineral added relative to the magnetic particles is preferably 4 vol% or more. Accordingly, in the formed coating layer 3, the width of the corner gap 239 mentioned above can be reduced, and the ratio of the thickness of the thick portion 36 to the thickness of the thin portion 37 can be reduced. The amount of clay mineral added relative to the magnetic particles is preferably 9 vol% or less, thereby preventing the viscosity of the slurry from being too high. The aforementioned added elements contained in the coating layer 3 are, in principle, elements derived from the above-mentioned clay minerals. In the present embodiment, the raw materials other than the clay minerals in the raw materials contained in the slurry contain almost no added elements.
[0063] After the slurry is prepared, the slurry is applied to the surface of the target compartment 23a of the substrate 2 (step S13). When the slurry is applied, the substrate 2 is erected in a manner such that the multiple compartments 23 face the vertical direction, as shown in FIG. Fig. 9 As shown, an upper clamp 81 and a lower clamp 82 are respectively installed on the upper and lower parts of the substrate 2. In detail, the upper clamp 81 is a roughly cylindrical component having an inner diameter slightly larger than the diameter of the substrate 2. An annular groove is provided at the lower part of the inner circumference of the upper clamp 81, and an annular rubber tube 811 is arranged in the groove. The upper clamp 81 is embedded in the upper part of the substrate 2 and contacts the outer circumference of the substrate 2 through the rubber tube 811. The lower clamp 82 is a roughly annular component having an inner diameter slightly smaller than the diameter of the substrate 2. A silicon O-ring 821 is provided on the upper surface of the lower clamp 82 and in a portion near the inner circumference. The substrate 2 is placed on the lower clamp 82, and the outer circumference of the lower end face 29 of the substrate 2 contacts the lower clamp 82 through the silicon O-ring 821.
[0064] After the upper fixture 81 and the lower fixture 82 are installed on the substrate 2, a specified amount of slurry is flowed into the interior of the upper fixture 81, and the slurry is filled on the upper end face 29 of the substrate 2. At this time, a coating material (not shown) covering the upper end face 29 is provided on the substrate 2, and a hole is formed in the portion of the coating material opposite to the target compartment 23a. Therefore, the slurry can only flow into the target compartment 23a. Next, a pump is used to evacuate the space on the lower end face 29 side of the substrate 2. As a result, the slurry flows into the target compartment 23a from the opening on the upper end face 29 side of the target compartment 23a, and the slurry is applied to the surface (inner peripheral surface) of the target compartment 23a. The slurry passing through the target compartment 23a flows out from the opening on the lower end face 29 side to the outside. After the slurry is applied to the target compartment 23a, the upper fixture 81 and the lower fixture 82 are removed from the substrate 2.
[0065] Next, the slurry applied to the target compartment 23a is dried. As described above, the shear strength of the slurry containing clay minerals is relatively high, so the slurry can be inhibited from agglomerating at the corner 231 due to surface tension. That is, the uniformity of the thickness of the dried slurry (uniformity in the circumferential direction of the target compartment 23a) is improved. The application and drying of the slurry can be repeated many times. Thereafter, sintering (heat treatment) is performed under a vacuum atmosphere. The sintering temperature is, for example, 1050 to 1250°C. The sintering time is, for example, 5 to 70 minutes. Thus, a coating layer 3 is formed on the surface of the target compartment 23a, and a honeycomb structure 1 is manufactured (step S14). The above-mentioned sintering temperature and sintering time are only examples and can be appropriately changed. It should be noted that it is believed that the clay minerals contained in the slurry are decomposed by sintering, and in the honeycomb structure 1, the clay minerals hardly exist in their own state.
[0066] Next, with reference to Table 1, Examples 1 to 9 and Comparative Examples 1 and 2 of the honeycomb structure of the present invention will be described.
[0067] Table 1
[0068]
[0069] <Production of Honeycomb Structure>
[0070] (Examples 1 to 9)
[0071] Weigh stainless steel (SUS430) powder as magnetic particles, montmorillonite as a clay mineral, and ion exchange water. In Table 1, the amount [vol%] of montmorillonite relative to the stainless steel powder in each of Examples 1 to 9 is shown in the "Montmorillonite Addition Amount" column, and the amount [parts by weight] of water relative to the stainless steel powder and montmorillonite is shown in the "Water Ratio" column. Put them together with ZrO2 balls (φ5mm) in a container, and mix them using a rotation and revolution mixer to prepare a slurry. Next, prepare a substrate whose interior is divided into multiple compartments by partitions. As shown in reference Fig. 9 As described, an upper clamp and a lower clamp are installed on the upper and lower parts of the substrate, respectively, and the slurry is applied to the surface of each compartment. Thereafter, the slurry is dried. In Table 1, the number of repetitions of applying and drying the slurry is shown in the "Number of Coatings" column. Next, sintering is performed in a vacuum atmosphere. In Table 1, the sintering temperature and sintering time are shown in the "Sintering Schedule" column. The heating rate is 500°C / hr. Through the above treatment, the honeycomb structures of Examples 1 to 9 are obtained.
[0072] (Comparative Examples 1-2)
[0073] Stainless steel (SUS430) powder, water-soluble adhesive, thickener and ion exchange water are weighed. In Comparative Examples 1 to 2, montmorillonite is not added to the slurry. They are placed in a container together with ZrO2 balls (φ5mm), mixed using a self-rotating and revolving mixer to prepare a slurry. The slurry is applied and dried in the same manner as in Examples 1 to 9. Thereafter, the substrate is kept at 180°C for 4 hours in an atmospheric atmosphere, and then kept at 450°C for 6 hours to perform degreasing. After degreasing, sintering is performed in the same manner as in Examples 1 to 9 to obtain the honeycomb structures of Comparative Examples 1 to 2.
[0074] <Measurement of coating layer>
[0075] For the honeycomb structures of Examples 1 to 9 and Comparative Examples 1 to 2, the ratio of the additive elements to the magnetic particles, the thickness of the coating layer, the relative density of the coating layer, the width of the corner gaps, and the thickness ratio of the thick part to the thin part were measured. In obtaining the ratio of the additive elements to the magnetic particles, the cross-section of the mirror-polished coating layer was measured using EDS and DX200s Digital Pulse Processor manufactured by RaySpec to determine the weight fraction of each main constituent element of the magnetic particles and the weight fraction of each additive element. Then, the sum of the weight fractions of the additive elements was divided by the sum of the weight fractions of the main constituent elements of the magnetic particles to obtain the ratio of the additive elements to the magnetic particles. Here, the main constituent elements of the magnetic particles are Fe and Cr, and the additive elements are Si, Al, and Mg. Therefore, in Table 1, the ratio of the additive elements to the magnetic particles is recorded as "(Si+Al+Mg) / (Fe+Cr)".
[0076] In Comparative Examples 1 to 2, the slurry does not contain montmorillonite, but at least one element among Si, Al and Mg is inevitably contained therein as an impurity, and therefore, (Si+Al+Mg) / (Fe+Cr) is greater than 0 wt% and less than 1.7 wt%. On the other hand, in Examples 1 to 9 in which the slurry contains montmorillonite, (Si+Al+Mg) / (Fe+Cr) is 1.7 wt% or more.
[0077] The thickness of the coating layer, the relative density of the coating layer, the width of the corner gap, and the thickness ratio of the thick part to the thin part were measured by using SEM (JSM-IT500 manufactured by JEOL), acquiring SEM images (magnification 500 times), and performing image analysis using image analysis software "Image-pro Premier 9.3" manufactured by MediaCybernetics. Figure 5 As described above, the distance between parallel lines along both surfaces of the thin portion in the SEM image showing the thin portion was measured as the thickness of the coating layer. Fig. 10A The SEM image of the subject compartment showing the coating layer thickness is less than 20 μm, Fig. 10B The SEM image of the subject compartment having a coating layer thickness of 20 μm or more is shown in FIG. Figure 4 As described, a calculation range including only the coating layer is set in the SEM image showing the thick portion, the calculation range is binarized using a threshold value that can distinguish the magnetic particles from other regions, and the area ratio of the region representing the magnetic particles is obtained as the relative density of the coating layer.
[0078] As reference Figure 7As described above, a tangent line is set in the SEM image showing the thick portion at an inclination angle of 45° relative to the flat portion and is tangent to the corner, and the shortest distance between the tangent line and the outer periphery of the thick portion is measured as the width of the corner gap. Figure 6 As described above, a tangent line is set in the SEM image showing the thick part, which is 45° inclined relative to the plane part and is tangent to the outer periphery of the thick part, and the shortest distance between the tangent line and the inner periphery of the thick part is measured as the thickness of the thick part. Then, the thickness of the thick part is divided by the thickness of the coating layer (thickness of the thin part) described above, thereby obtaining the thickness ratio of the thick part to the thin part. Fig.11A The SEM image of the subject cell in which the width of the corner gap is greater than 15 μm and the thickness ratio of the thick part to the thin part is greater than 2 times is shown in FIG. Fig. 11B ] shows an SEM image of a target cell in which the width of the corner void is 15 μm or less and the thickness ratio of the thick portion to the thin portion is 2 times or less.
[0079] <Evaluation of induction heating characteristics>
[0080] like Fig.12 As shown, a honeycomb structure 1 is arranged inside an induction heating coil 71. The induction heating coil 71 is driven for 180 seconds at a frequency of 100 kHz and a power of 0.5 kW, and the reaching temperature is measured by a thermocouple 72 provided inside the honeycomb structure 1. As shown in Table 1, the reaching temperatures of the honeycomb structures of Examples 1 to 5, 7 to 9 and Comparative Examples 1 to 2 are all above 390°C. On the other hand, the reaching temperature of the honeycomb structure of Example 6 in which the thickness of the coating layer is less than 20 μm is 210°C.
[0081] <Evaluation of thermal shock resistance>
[0082] Using a furnace bottom lifting furnace maintained at 700°C, the furnace bottom carrying the honeycomb structure was moved up and down for evaluation. Specifically, the furnace bottom was positioned at the ascending end, and the honeycomb structure was maintained in the furnace for 10 minutes. After that, the furnace bottom was positioned at the descending end, and the honeycomb structure was placed outside the furnace (room temperature atmosphere), and air was blown for 5 minutes using a blower. The above-mentioned hot and cold cycles were performed for 100 cycles, and then the appearance of the honeycomb structure was observed. In Table 1, when cracks were confirmed in the honeycomb structure, the evaluation result was set to ×, and when no cracks were confirmed, the evaluation result was set to ○. In the honeycomb structures of Examples 1 to 9, the evaluation result of heat shock resistance was ○, while in the honeycomb structures of Comparative Examples 1 to 2, the evaluation result of heat shock resistance was ×. It should be noted that it can be said that the honeycomb structure with a heat shock resistance evaluation result of ○ also has repeated durability against heat shock.
[0083] <Consideration of coating layer>
[0084] In the honeycomb structures of Comparative Examples 1 and 2 in which the slurry does not contain clay minerals, the slurry is easily condensed toward the corners due to surface tension immediately after the slurry is applied, and the thickness of the slurry is too thick at the corners and too thin at the flat parts. During the firing of the slurry, a large gap is generated between the surface of the corner of the target cell and the coating layer due to the firing shrinkage. As a result, it is believed that in the evaluation of heat shock resistance, stress concentration occurs at the boundary between the contact part and the non-contact part (the above-mentioned gap) between the coating layer and the cell surface, and cracks are easily generated in the substrate.
[0085] In contrast, in Examples 1 to 9, montmorillonite as a clay mineral is added to the slurry, whereby the slurry becomes a Bingham fluid, and the shear stress acts in a static state. That is, the slurry does not flow before the shear stress exceeds the yield value, and the slurry can be inhibited from agglomerating toward the corners due to surface tension just after the slurry is applied. In addition, it can be seen that by adding montmorillonite to the slurry, the relative density of the magnetic particles before sintering after drying increases, and the sintering shrinkage decreases. In addition, it is confirmed that montmorillonite decomposes and produces gas during sintering, and closed pores are easily generated in the coating layer due to the generation of the gas, and the excessive densification of the magnetic particles is suppressed. In this regard, the sintering shrinkage is also reduced. As a result, it is believed that compared with Comparative Examples 1 to 2, the adhesion of the coating layer at the corner is improved, the gap between the corner and the coating layer is reduced, and the cracks caused by stress concentration in the evaluation of heat shock resistance are suppressed.
[0086] In the honeycomb structure of Example 6, the thickness of the coating layer is relatively small (less than 20 μm), so the reaching temperature in the induction heating characteristic evaluation is greatly reduced. Therefore, it can be said that in order to increase the reaching temperature, the thickness of the coating layer is preferably 20 μm or more. In the honeycomb structure of Example 7, the thickness of the coating layer is 50 μm, but the reaching temperature is lower than 400°C, which is relatively low. It is believed that the reason is that in Example 7, the relative density of the coating layer is relatively small (less than 75%), so the connectivity between the magnetic particles is low and the eddy current is not easy to flow. In other words, it can be said that in order to increase the reaching temperature, it is preferred to set the relative density of the coating layer to 75% or more to increase the filling rate of the magnetic particles.
[0087] As described above, the honeycomb structure 1 comprises: a substrate 2 which is a cylindrical member and is provided with a plurality of cells 23 extending from one end face 29 to another end face 29; and a coating layer 3 which is provided on the surface of the target cell 23a which is at least a part of the plurality of cells 23 and is obtained by bonding magnetic particles 31 to each other. The coating layer 3 contains at least one element of Si, Al and Mg as an additive element. In the coating layer 3, the ratio of the sum of the weight fractions of the additive elements to the sum of the weight fractions of the main constituent elements of the magnetic particles 31 is 1.7 wt% or more. Accordingly, a honeycomb structure 1 having high thermal shock resistance (including repeated durability against thermal shock) can be provided.
[0088] Preferably, the maximum width of the gap between the surface of the target cell 23a and the coating layer 3 is 15 μm or less, and / or the ratio of the thickness of the thick portion 36 to the thickness of the thin portion 37 in the target cell 23a is 2 times or less. Thus, the thermal shock resistance of the honeycomb structure 1 can be more reliably improved.
[0089] Preferably, the relative density of the coating layer 3 is 75 to 95%, and / or the thickness of the coating layer 3 is 20 to 100 μm. Thereby, the reaching temperature of the honeycomb structure 1 can be increased during induction heating.
[0090] Preferably, the main constituent elements of the magnetic particles 31 are Fe and Cr. In the magnetic particles 31, the balance between the resistivity and the magnetic permeability is good, and the heating efficiency is improved. In addition, when the magnetic particles 31 contain Cr, the coating layer 3 having excellent corrosion resistance is obtained.
[0091] Preferably, in the coating layer 3, the compound containing the additive element is present on the surface of the magnetic particles 31. Accordingly, the structure of the coating layer 3 containing the magnetic particles 31 (i.e., the connectivity of the magnetic particles 31, the shape of the coating layer 3, the relative density, etc.) can be controlled by using the compound to hinder the sintering of the magnetic particles 31 to a certain extent.
[0092] The method for manufacturing the honeycomb structure 1 includes: a step of preparing a substrate 2 provided with a plurality of cells 23 (step S11), a step of preparing a slurry containing magnetic particles and clay minerals (step S12), a step of applying the slurry on the surface of at least a portion of the cells 23, i.e., the target cells 23a (step S13), and a step of drying and firing the slurry applied to the target cells 23a to form a coating layer 3 on the surface of the target cells 23a (step S14). Thus, a honeycomb structure 1 having high thermal shock resistance can be provided.
[0093] Preferably, the clay mineral includes at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite, and attapulgite. Thereby, the thermal shock resistance of the honeycomb structure 1 can be more reliably improved.
[0094] The above-mentioned honeycomb structure 1 and the method for manufacturing the honeycomb structure 1 can be variously modified.
[0095] In order to realize high thermal shock resistance in the honeycomb structure 1, the relative density of the coating layer 3 may be outside the range of 75 to 95%, and the thickness of the coating layer 3 may be outside the range of 20 to 100 μm. In addition, the maximum width of the gap between the surface of the target cell 23a and the coating layer 3 may be greater than 15 μm, and the thickness of the thick portion 36 may be greater than twice the thickness of the thin portion 37.
[0096] The honeycomb structure 1 can be used to remove Figure 8 The honeycomb structure 1 can be used for purposes other than the catalyst carrier.
[0097] The configurations in the above-described embodiment and each modified example may be appropriately combined unless they are mutually contradictory.
Claims
1. A honeycomb structure, wherein: have: A substrate, which is a cylindrical member and is provided with a plurality of compartments extending from one end face to another end face; as well as a coating layer, which is provided on the surface of at least a part of the plurality of compartments, namely the target compartment, and is formed by bonding magnetic particles to each other, The coating layer contains at least one element of Si, Al and Mg as an additive element, In the coating layer, a ratio of the sum of weight fractions of the additional elements to the sum of weight fractions of main constituent elements of the magnetic particles is 1.7 wt % or more.
2. The honeycomb structure according to claim 1, wherein The main constituent elements of the magnetic particles are Fe and Cr.
3. The honeycomb structure according to claim 1, wherein In the coating layer, the compound containing the additional element is present on the surface of the magnetic particle.
4. The honeycomb structure according to any one of claims 1 to 3, wherein: The relative density of the coating layer is 75-95%.
5. The honeycomb structure according to any one of claims 1 to 3, wherein: The coating layer has a thickness of 20 to 100 μm.
6. The honeycomb structure according to any one of claims 1 to 3, wherein: The maximum width of the gap between the surface of the subject cell and the coating layer is 15 μm or less.
7. The honeycomb structure according to any one of claims 1 to 3, wherein: The coating layer has a thick portion with a locally maximum thickness and a thin portion with a locally minimum thickness, The ratio of the thickness of the thick portion to the thickness of the thin portion is 2 times or less.
8. A method for manufacturing a honeycomb structure, wherein: Including the following processes: a) preparing a substrate, which is a cylindrical member and is provided with a plurality of compartments extending from one end face to another end face; b) preparing a slurry comprising magnetic particles and clay minerals; c) applying the slurry on the surface of at least a portion of the plurality of compartments, i.e., the target compartment; as well as d) drying and firing the slurry applied to the target cell, thereby forming a coating layer on the surface of the target cell.
9. The method for manufacturing a honeycomb structure according to claim 8, wherein: The clay mineral includes at least one selected from the group consisting of montmorillonite, sepiolite, hectorite, halloysite, and attapulgite.
Citation Information
Patent Citations
Catalyst carrier and method for producing same, and exhaust gas purification device
JP2019188272A
Catalyst carrier, method of manufacturing same, and exhaust gas purification apparatus
CN110385148A
Honeycomb structure and exhaust gas purification device
CN114302764A